The Effect Of Cooperative Learning Type Numbered Head Together (NHT)Toward In Activities Improvement and Matter Material Mastery Of The Creatures Growth and Development - Aria Seprinda; Pramudiyanti Pramudiyanti; Rini Marpaung (Universitas Lampung, 2013)
Learning activity and student material mastery In Junior High School 2 Tulang Bawang Tengah are still low. One of alternative to increase the activity and matter material mastery of the Creatures Growth and Development by students which are Numbered Head Together (NHT) learning model, a learning model that can be increases learning activity even though effecting to students. Experimental design uses pretest posttest non equivalent group. The sample in this study is VIII D as a experimental class and VIII E as a control class which choose by cluster random sampling. The quantitative data is taken from the average of pre-test and post-test point and then analyzed with statistic using T-test by SPSS 17 program. The qualitative data is learning activity student which taken from observation paper as long as learning activity. The result of this study are showing the application of NHT learning models have a significant impact to increase learning activity and mastery student matter. For seen, N-gain average experiment class is 53,6. The percentage average of student learning activity in experiment class which used NHT learning model are high category 12,91 %. Keywords: NHT learning model, student learning activity, student matter mastery and material of the Creatures Growth and Development